A novel approach to the analysis of squeezed-film air damping in microelectromechanical systems. (2nd November 2016) - Yang, Weilin; Li, Hongxia; Chatterjee, Aveek N; Elfadel, Ibrahim (Abe) M; Ocak, Ilker Ender; Zhang, TieJun
Abstract: Squeezed-film damping (SFD) is a phenomenon that significantly affects the performance of micro-electro-mechanical systems (MEMS). The total damping force in MEMS mainly include the viscous damping force and elastic damping force. Quality factor ( Q factor) is usually used to evaluate the damping in MEMS. In this work, we measure the Q factor of a resonator through experiments in a wide range of pressure levels. In fact, experimental characterizations of MEMS have some limitations because it is difficult to conduct experiments at very high vacuum and also hard to differentiate the damping mechanisms from the overall Q factor measurements. On the other hand, classical theoretical analysis of SFD is restricted to strong assumptions and simple geometries. In this paper, a novel numerical approach, which is based on lattice Boltzmann simulations, is proposed to investigate SFD in MEMS. Our method considers the dynamics of squeezed air flow as well as fluid-solid interactions in MEMS. It is demonstrated that Q factor can be directly predicted by numerical simulation, and our simulation results agree well with experimental data. Factors that influence SFD, such as pressure, oscillating amplitude, and driving frequency, are investigated separately. Furthermore, viscous damping and elastic damping forces are quantitatively compared based on comprehensive simulation. The proposed numerical approach as well as experimental characterization enables us to reveal the insightful physics of squeezed-film air damping in MEMS.